A case of malonyl coenzyme A decarboxylase deficiency with novel mutations and literature review - Zhao, Cong; Peng, Hua; Jiang, Nanchuan; Liu, Yalan; Chen, Yan; Liu, Jie; Guo, Qing; Wu, Zubo; Wang, Lin (Frontiers in Pediatrics, 2023)
Malonyl coenzyme A decarboxylase deficiency is caused by an abnormality in the MLYCD gene. The clinical manifestations of the disease include multisystem and multiorgan involvement. In this paper, we report a 3-year-old girl who is presented with developmental delay, myocardial damage and elevated C3DC. High-throughput sequencing identified heterozygous mutations from the patient’s parents (c. 641+5 G>C, c. 798 G>A), which was the first report of this locus, adding a new item to the MLYCD mutation library. RNA-seq showed that there were 254 differential genes in this child, among which 153 genes were up-regulated and 101 genes were down-regulated. Exon jumping events occurred in exons encoding PRMT2 on the positive chain of chromosome 21, which led to abnormal splicing of PRMT2. (P<0.05, FDR<0.05). The result of SNP showed that there were multiple mutation sites on chromosome 1, which may affect the downstream gene variation at the DNA level. We also provide a comprehensive literature review of reported cases. The literature review identified 54 cases described since 1984. Developmental delay and cardiomyopathy are the most common clinical manifestations, with commonly elevated malonate and malonyl carnitine levels in children.